REPRESENTATION OF VAT INCREASE (12%) IN REALIZING JUSTICE AND WELFARE OF THE INDONESIAN PEOPLE - Maulia Regita Belananda; Alfiaturrizqi (ASIAN PUBLISHER, 2025)
This research focuses on the representation of the 12% increase in Value Added Tax (VAT) on the justice and welfare of the Indonesian people. The purpose of this study is to evaluate the explicit and implicit impact of VAT increase policies and assess the extent to which these policies contribute to social justice and people's welfare. The research method used is a qualitative method with a literature study approach. The data collection is from various sources of books, journals, theses, magazines, articles, or other relevant online sources. The results of the study show that the increase in VAT has a direct impact on increasing the price of goods and services, which has the potential to reduce people's purchasing power, especially the lower middle economic group. In addition, indirect impacts include the possibility of increased inflation as well as changes in people's consumption patterns. Although this policy aims to increase state revenues to support development, its effectiveness in realizing people's welfare still depends on the implementation of compensation programs, such as subsidies and social assistance. Thus, there is a need for additional policies to ensure that the increase in VAT does not exacerbate social and economic inequality in Indonesia.